A numerical simulation study of particulate collection by vegetative barriers. (October 2019) - Ma, Shuli; Maghirang, Ronaldo; Zhao, Dongsen; Liu, Xiaolin; Wang, Chun; Guo, Li
Abstract : Previous research has shown that particulate matter (PM) in the air can be captured by vegetative barriers (VB) serving as shelter against the wind; however, there is only limited research of factors affecting their efficiency. This study used computational fluid dynamics to predict particle collection efficiency (CE) of VBs, as affected by hedge geometry (i.e., the size expressed in terms of height, depth, and leaf surface area density [LSAD]) and the number of hedgerows. The experimental data of Tiwary et al. (Journal of Aerosol Science, 2005) were used for model parametrisation. The area of wind speed reduction, protection area and mean collection efficiency were defined and calculated to evaluate the effectiveness of VBs on sheltering function and particle collection. Simulation results predicted that compared with original size, increasing the height and LSAD of the hedge resulted in a greater decrease of wind speed. Increasing the depth of the hedge had the greatest effect on particle collection with 42.4% for dp  = 15 μm, more effective than increasing the height or LSAD. Adding another row of hedge also increased the capability of the hedge in wind speed reduction and particle collection, while row spacing did not show great effect. The increasing rate of mean CE by adding a hedgerow was less than that by increasing hedge size, which more than double the CE of particles with diameter greater than 4.25 μm. Field measurements and additional simulation tests need to be conducted under different conditions for model validation. Highlights: Increasing the height of hawthorn VB had the best effect on sheltering function. Doubling the width of the VB had the greatest effect on filtering coarse particle. Adding a row of VB was not as effective as enlarging size on collecting particle.